Probiotic growth pattern and physicochemical evaluation of water kefir fermentation - Sin, Phin Yin; Tan, Suat Hian; Mohd Fazli, Farida Asras; Lee, Chin Mei; Muhammad Adam lee, Abdullah (Malaysian Society of Applied Biology, 2024)
Probiotics are live-friendly microorganisms that can confer a health benefit on the host if it is consumed in sufficient amounts. Water kefir is a probiotic-rich fermented beverage that contains multi-species of live cultures. Brown sugar and palm sugar were used for water kefir fermentation due to their high sucrose and mineral contents. The objective of this study was to determine the probiotic growth pattern of water kefir and to evaluate the physicochemical parameters, including the pH changes, lactic acid content, reducing sugar content, and total soluble solids. The fermented water kefir was collected at every 6-hour interval, until the end of 72 hours of fermentation. The growth curve was determined by enumerated probiotics on De Man, Rogosa, and Sharpe (MRS) agar, Yeast Extract-Peptone-Dextrose (YPD) agar, and Gluconobacter (GM) agar plates, respectively. MRS, YPD, and GM agar plates were used to enumerate lactic acid bacteria, yeast, and acetic acid bacteria, respectively. The result showed increased probiotic growth as fermentation time increased with different phases observed from the growth curve. The stationary phase of probiotics was recorded at 30-42 h and was recommended as the optimal harvesting point. Besides, longer fermentation time produced lower pH values and lower total soluble solids while higher lactic acid and higher reducing sugars. At the end of fermentation, the concentration of lactic acid and reducing sugars were 2.16 ± 0.09 g/L and 13.66 ± 0.14 mg/mL, respectively. In conclusion, probiotics from water kefir fermentation are suggested to be best harvested between 30-42 hours and can be used for self-consume or downstream processing.